2017
DOI: 10.36076/2017.1.e137
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Variants of the Pudendal Nerve Observed during a Transgluteal Surgical Approach in a Population of Patients with Pudendal Neuralgia

Abstract: Background: Several studies have described the course and anatomical relations of the pudendal nerve. Several surgical nerve decompression techniques have been described, but only the transgluteal approach has been validated by a prospective randomized clinical trial. The purpose of this study was to describe the course of the nerve and its variants in a population of patients with pudendal neuralgia in order to guide the surgeon in the choice of surgical approach for pudendal nerve decompression. Objectives: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 11 publications
0
34
0
12
Order By: Relevance
“…The pudendal nerve originates from ventral rami S2 to S4 in most cases to take a lateral course and pass dorsally or in close proximity medial to the ischial spine. Nevertheless, variants have been found that pierce the SSL (Ploteau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The pudendal nerve originates from ventral rami S2 to S4 in most cases to take a lateral course and pass dorsally or in close proximity medial to the ischial spine. Nevertheless, variants have been found that pierce the SSL (Ploteau et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it does not permit to anticipate eventual anatomical variations of the branches of the pudendal nerve, described in up to 13% of the cases in literature. 11 Another endoscopic anterolateral approach of the region has been described for sciatic nerve decompression. 19,20 Here, the trocar site is too distal and anterior to allow visualisation of the anatomy we are interested in.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Several authors have reported a number of anatomical variants of the pudendal nerve: variants affecting the origin of the nerve in the sacral plexus, and variants in terms of length, diameter, number of branches, and distribution. [11][12][13][14][15] The posterior femoral cutaneous nerve classically arises from the sacral plexus, predominantly from the S2 nerve root. It then accompanies the sciatic nerve, usually coursing medial or posterior to this nerve.…”
Section: Normal Topographic Anatomy Of the Pudendal Nerve (Pn) And mentioning
confidence: 99%
See 2 more Smart Citations